2004
DOI: 10.2298/vsp0404359k
|View full text |Cite
|
Sign up to set email alerts
|

Presence of interleukin-8 and the IL-1 receptor antagonist in the cervical mucus of fertile and infertile women

Abstract: Changes in IL-8 and IL-1Ra levels in the cervical mucus of infertile patients with negative postcoital test suggested the existence of the relationship between cervical cytokines and infertility in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mid-cycle cervical mucus adversely affected the bioactive properties of IL-4 and the immunoglobulins IgA and IgG by decreasing their recovery from aqueous media after contact [24]. Cervical mucus contains antagonists of two key inflammatory cytokines, IL-8 and IL-1, both involved in the recruitment of phagocytic and inflammatory cell types [25]. Thus mucus may regulate immune parameters in the female reproductive tract by both physical and biochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-cycle cervical mucus adversely affected the bioactive properties of IL-4 and the immunoglobulins IgA and IgG by decreasing their recovery from aqueous media after contact [24]. Cervical mucus contains antagonists of two key inflammatory cytokines, IL-8 and IL-1, both involved in the recruitment of phagocytic and inflammatory cell types [25]. Thus mucus may regulate immune parameters in the female reproductive tract by both physical and biochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…When the abundance of IL6 and IL8 in the serum and cervical mucus of infertile women were compared with that of matched fertile women, a significantly higher concentration of both cytokines were found among infertile women, suggesting a probable role in the etiology of female infertility (Naz and Butler, ). Subsequent studies support this relationship, particularly for IL8 (Spandorfer et al, ; Kataranovski et al, ). Another study reported that oocyte fertilization rates in patients with endometriosis are markedly lower than those with tubal infertility (Xu et al, ), suggesting that recruitment of cytokines near or into the ovary may also impair oocyte quality.…”
Section: Cytokinesmentioning
confidence: 87%